REGULASI DIRI PADA MAHASISWA BERPRESTASI - Alivermana Wiguna; Gita Anggraini; Kholidiyah Apriyani (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
Self regulation is self-management in achieving a goal in the situation of various activities. The purpose of this study was to determine self-regulation of high achieving students. This research is a qualitative research with a phenomenological approach. Data collection in this study uses the interview method and the problem checklist model. The better the level of self-regulation of individuals, the better in managing themselves to achieve predetermined goals. The results of the study showed that the self regulation of one of the outstanding students was included in the good category. This means that the student has been able to manage himself and direct his thoughts and actions to achieve goals including achievement.